Negatieve exponent (reeks 1)

Hoofdmenu Eentje per keer 

Zet om naar een positieve exponent

  1. \((-1)^{-3}\)
  2. \((-14)^{-4}\)
  3. \((-19)^{-4}\)
  4. \(-14^{-2}\)
  5. \(-10^{-1}\)
  6. \(4^{-3}\)
  7. \(-4^{-4}\)
  8. \((2)^{-1}\)
  9. \(-2^{-4}\)
  10. \((-5)^{-4}\)
  11. \((-6)^{-2}\)
  12. \(-6^{-1}\)

Zet om naar een positieve exponent

Verbetersleutel

  1. \((-1)^{-3}=\left(-\frac{1}{1}\right)^{3}=- \frac{1}{1^{3}}=-1\)
  2. \((-14)^{-4}=\left(-\frac{1}{14}\right)^{4}= \frac{1}{14^{4}}=\ldots \text{ZRM}\)
  3. \((-19)^{-4}=\left(-\frac{1}{19}\right)^{4}= \frac{1}{19^{4}}=\ldots \text{ZRM}\)
  4. \(-14^{-2}=-\left(\frac{1}{14}\right)^{2}=- \frac{1}{14^{2}}=- \frac{1}{196}\)
  5. \(-10^{-1}=-\left(\frac{1}{10}\right)^{1}=- \frac{1}{10^{1}}=- \frac{1}{10}\)
  6. \(4^{-3}=\left(\frac{1}{4}\right)^{3}= \frac{1}{4^{3}}=\ldots \text{ZRM}\)
  7. \(-4^{-4}=-\left(\frac{1}{4}\right)^{4}=- \frac{1}{4^{4}}=\ldots \text{ZRM}\)
  8. \((2)^{-1}=\left(\frac{1}{2}\right)^{1}= \frac{1}{2^{1}}= \frac{1}{2}\)
  9. \(-2^{-4}=-\left(\frac{1}{2}\right)^{4}=- \frac{1}{2^{4}}=- \frac{1}{16}\)
  10. \((-5)^{-4}=\left(-\frac{1}{5}\right)^{4}= \frac{1}{5^{4}}=\ldots \text{ZRM}\)
  11. \((-6)^{-2}=\left(-\frac{1}{6}\right)^{2}= \frac{1}{6^{2}}= \frac{1}{36}\)
  12. \(-6^{-1}=-\left(\frac{1}{6}\right)^{1}=- \frac{1}{6^{1}}=- \frac{1}{6}\)
Oefeningengenerator vanhoeckes.be/wiskunde 2022-06-27 08:26:55